The impact of inattention, hyperactivity/impulsivity symptoms, academic achievement, and gender on the self-esteem: a study of children in Japanese elementary schools - Chie Miyadera (Cogent Psychology)
The intensity of attention-deficit/hyperactivity disorder (ADHD) symptoms in children not diagnosed with ADHD has been associated with low self-esteem. This study examined gender-based self-esteem differences in elementary school children and analyzed the relationships among inattention, hyperactivity/impulsivity symptoms, academic achievement, school experience, and perceived social support on self-esteem.The participants were 150 fifth- and sixth-grade Japanese elementary school children (70 boys and 80 girls), paired with a parent. Parents described their children’s inattention, hyperactivity/impulsivity symptoms, and academic achievement, while children self-rated their self-esteem, school experiences, and perceived social support from parents, teachers, and friends. The t-test results indicated significant differences between boys and girls in hyperactivity/impulsivity symptoms, friend-related experiences, and perceived social support from teachers and friends. Perceived social support from friends was strong for girls, and that from teachers was strong for boys. The correlation analyses showed that self-esteem linked to academic skills was significantly correlated with academic achievement and academic-related experience for both genders. Academic achievement was a strong predictor of self-esteem concerning academic skills for girls and boys, respectively. Additionally, in boys, inattention and hyperactivity/impulsivity symptoms had greater power than academic achievement in predicting self-esteem regarding athletic skills. Therefore, the findings suggested that academic achievement played an essential role in self-esteem regarding academic skills. Our results showed that academic-related experiences and perceived support were also important factors. In the future, we would like to examine these subjective indicators in light of their impact on objective indicators such as academic achievement.